Effect of 12 Weeks Aerobic Exercise in morning and afternoon on Diabetic Women's protein Catabolism - Hassan Darvakh; Asiehsadat Mousavian (Mashhad University of Medical Sciences, 2017)
Introduction: Diabetes Mellitus includes a group of prevalent metabolic (metabolism) disorders which may occur in fat and protein metabolism. According to the research of specialists, regular exercise is essential to control and improve diabetes. Therefore, this study was performed with aim to evaluate the effect of circadian rhythm during 12 weeks of aerobic exercise on protein catabolism of type 2 diabetic women. Methods: This semi-experimental study was conducted on 45 women with diabetes in Behbahan at 20116. They were randomly divided into two experimental groups (n=15 in each group) of aerobic training in morning and afternoon and control group. The experimental group underwent selective aerobic exercise with the intensity of 55-70%, the maximum heart beat and the increasing time of 35-50 minutes per session. The activity intensity was added up to 5% every four weeks. After 15 minutes of walking briskly, the exercise included aerobics and coordinated movements of hands and feet. The control group didn't have exercise during 12 weeks. 24 hour urine urea test was measured and assessed in the first and 12th week. Data was analyzed by SPSS Software (version 16) and ANOVA and LSD tests. P<0.05 was considered significant. Results: The selective aerobic exercise for 12 weeks in the morning and afternoon significantly reduced 24 hour urine urea level of the subjects compared with control group (P≥0.05). No significant difference was observed in 24 hour urine urea level of the subjects between aerobic exercise in the morning and the afternoon (P≤0.05). Conclusion: Exercise both in the morning and the afternoon was almost equally effective on diabetic women's protein catabolism.